Major hurdles to the use of tyrosine kinase inhibitors in clinical prevention/interception studies: Do preclinical studies with EGFR inhibitors suggest approaches to overcome some of the limitations - Dragnev, Konstantin H.; Dragnev, Christo P. C.; Lubet, Ronald A. (Frontiers in Cell and Developmental Biology, 2023)
There are major hurdles to the use of tyrosine kinase inhibitors (TKIs) and any other agents with significant toxicities (which means practically the preponderance of potential effective agents) in the context of prevention/anti-progression (interception) studies. We will discuss epidermal growth factor receptor (EGFR) inhibitors as examples, both in a primary prevention setting, where agent(s) are administered to individuals with no cancer but who might be considered at higher risk due to a variety of factors, and in anti-progression/interception studies, where agent(s) are administered to persons with known preinvasive lesions (e.g. colon adenomas, lung nodules, ductal carcinoma in situ (DCIS), or pancreatic intraepithelial neoplasia (PanIN) lesions in the pancreas) in an attempt to reverse or inhibit progression of these lesions. Multiple potential hurdles will be examined, including: a) toxicity of agents, b) the likely range of subtypes of cancers affected by a given treatment (e.g. EGFR inhibitors against EGFR mutant lung adenocarcinomas), c) the availability of practical endpoints besides the blocking of cancer formation or pharmacokinetics related to the agents administered in a primary prevention study, and d) the interpretation of the regression or blockage of new preinvasive lesions in the anti-progression study. Such an anti-progression approach may help address some of the factors commented on regarding primary prevention (toxicity, potential target organ cancer subtypes) but still leaves major questions regarding interpretation of modulation of preinvasive endpoints when it may not be clear how frequently they progress to clinical cancer. Additionally, we address whether certain recent preclinical findings might be able to reduce the toxicities associated with these agents and perhaps even increase their potential efficacy. Antibodies and TKIs other than the EGFR inhibitors are not discussed because few if any had been tested as monotherapies in humans, making their efficacy harder to predict, and because a number have relatively rare but quite striking toxicities. Furthermore, most of the practical hurdles raised regarding the EGFR inhibitors are relevant to the other TKIs. Finally, we briefly discuss whether early detection employing blood or serum samples may allow identification of high-risk groups more amenable to agents with greater toxicity.